BIOREMEDIASI LIMBAH PEMBORAN MINYAK DI JOB PERTAMINA – PETROCHINA EAST JAVA TUBAN - JAWA TIMUR: BIOREMEDIATION OF OIL DRILLING WASTE AT JOB PERTAMINA – PETROCHINA EAST JAVA TUBAN - EAST JAVA - Ai Siti Patimah (Universitas Papua, 2015)
The research has been conducted in field scales with comparative descriptive analysis method, using landfarming bioremediation process by mixing oil sludge and soil to reduce water content in mud. To fix the soilporosity compost has been added, this become he end-product bulking agent as well as nutrient sources fordegradation microorganism. The sludge came from Sukowati #4,#6, and #7 oil well JOB Pertamina –PetroChina Tuban, East Java. The goals of the research are to study indigenous microorganism from the wells,to understand the degradation differences between wells, and the benefits of bioremediation for the society. Thefactors that influenced the microorganism oil degradation performance are end-product compost, and organicfertilizer. The society could use the bioremediation water for land filling and bricks. The more time materialgiven for the material to degrade the better the result